PRODUKTIVITAS PEMANENAN KAYU DENGAN TEKNIK RIL DI PT. WIJAYA SENTOSA, PAPUA BARAT - Aurora Putri Modi Sandiana BES; Muhammad Helmi; Fonny Rianawati (Jurnal Sylva Scienteae, 2021)
The aim of this study is to measure the productivity of forest harvesting activities that consist of logging, skidding, loading, hauling, and unloading using the Reduced Impact Logging (RIL) technique in the natural forest of PT. Wijaya Sentosa, West Papua. The location of the study was determined by simple random sampling for 3 days for each activity, at 3 different subplots, also with different logging operator, skidding operator, and hauling driver. The final results of this research are productivity for loading using STIHLL 072 chainsaw is 5.74 m3/hour, productivity of skidding using Caterpillar 527 skidder winch is 11.43 m3/hour, productivity of loading using wheel loader 980F is 117.80 m3/hour, productivity of unloading using wheel loader 980F is 196.14 m3/hour, productivity of hauling using Mercedes Benz Actross logging truck is 15.62 m3/hour, and productivity of hauling using Mercedes Benz 3836AK logging truck is 16.34 m3/hour.Keywords: Productivity; Forest Harvesting; RIL (Reduced Impact Logging) Technique